Metagenomic Characterization of Influenza Virus: Bacteria Super-Infections Associated With Death and Survival. (11th September 2019) - Klonoski, Josh; Williams, Matthew; Huber, Victor
Abstract: Bacterial super-infections (BSIs) increase morbidity and mortality during influenza epidemics and pandemics, but not all strains of influenza virus uniformly increase host susceptibility to BSIs. Infection of mice with a swine virus isolate, A/swine/Texas/4199-2/98-H3N2 (TX98), did not significantly predispose the host to BSI mortality regardless of whether the BSI was caused by S aureus, S pneumoniae, or S pyogenes . Comparison of this survival phenotype with the laboratory influenza virus strain A/Puerto Rico/3/1934-H1N1, which demonstrates lethal synergism, showed that cellular recruitment profiles and cytokine responses differ between the two viruses in a manner that implicates host responses against the invading virus as a contributor to secondary infection severity. To better understand host, viral, and bacterial responses underlying disparate outcomes, we utilized metagenomic analysis of 559 genes, the NanoString nCounter Immunology Panel-Plus kit and FFPE mouse lungs from a published BSI time course. Results show an overall increased level of gene expression during BSIs associated with survival when compared to peak viral titers. Early viral clearance and the presence of S pyogenes in the lungs of TX98-infected lungs 24 hours after BSI was confirmed. Host responses tied to differences in early viral detection and clearance consisted of RIG-I, OAS, TLR3, TLR8, and TLR9. Key changes were noted in the expression of type I and II interferons, complement proteins, cytokines, chemokines, Fc receptors, scavenger receptors, the immunoproteasome, and genes associated with T, B, Treg, and NK cell activation. Interestingly, there was no significant increase in host antimicrobial peptides during BSIs associated with survival while CAMP and Nos2 were significantly increased 24 hours prior to death in lethal BSIs. To our knowledge, this is the first side-by-side metagenomics study of influenza BSIs associated with death and survival. Results offer mechanistic insight into clinical outcomes.